An integrated public health response to an outbreak of Murray Valley encephalitis virus infection during the 2022–2023 mosquito season in Victoria - Braddick, Maxwell; O’Brien, Helen M.; Lim, Chuan K.; Feldman, Rebecca; Bunter, Cathy; Neville, Peter; Bailie, Christopher R.; Butel-Simoes, Grace; Jung, Min-Ho; Yuen, Aidan; Hughes, Nicole; Friedman, N. Deborah (Frontiers in Public Health, 2023)
Introduction Murray Valley encephalitis virus (MVEV) is a mosquito-borne flavivirus known to cause infrequent yet substantial human outbreaks around the Murray Valley region of south-eastern Australia, resulting in significant mortality. Methods The public health response to MVEV in Victoria in 2022–2023 included a climate informed pre-season risk assessment, and vector surveillance with mosquito trapping and laboratory testing for MVEV. Human cases were investigated to collect enhanced surveillance data, and human clinical samples were subject to serological and molecular testing algorithms to assess for co-circulating flaviviruses. Equine surveillance was carried out via enhanced investigation of cases of encephalitic illness. Integrated mosquito management and active health promotion were implemented throughout the season and in response to surveillance signals. Findings Mosquito surveillance included a total of 3,186 individual trapping events between 1 July 2022 and 20 June 2023. MVEV was detected in mosquitoes on 48 occasions. From 2 January 2023 to 23 April 2023, 580 samples (sera and CSF) were tested for flaviviruses. Human surveillance detected 6 confirmed cases of MVEV infection and 2 cases of “flavivirus-unspecified.” From 1 September 2022 to 30 May 2023, 88 horses with clinical signs consistent with flavivirus infection were tested, finding one probable and no confirmed cases of MVE. Discussion The expanded, climate-informed vector surveillance system in Victoria detected MVEV in mosquitoes in advance of human cases, acting as an effective early warning system. This informed a one-health oriented public health response including enhanced human, vector and animal surveillance, integrated mosquito management, and health promotion.